Credit Cardhotders: Distinguishing The Good Apples From The Bad Apples. - Cheu, See Peng; Loke, Yiing Jia (2008)
Credit card is a double-edged sword. While the credit facilities offered by credit card provide liquidity for unforeseen circumstances, it also tempts one to overspend.